Differential activation of G protein‐mediated signaling by synthetic cannabinoid receptor agonists. Issue 2 (26th February 2020) - Sachdev, Shivani; Banister, Samuel D.; Santiago, Marina; Bladen, Chris; Kassiou, Michael; Connor, Mark
Abstract: Synthetic cannabinoid receptor agonists (SCRAs) are new psychoactive substances associated with acute intoxication and even death. However, the molecular mechanisms through which SCRAs may exert their toxic effects remain unclear—including the potential differential activation of G protein subtypes by cannabinoid receptor type 1 (CB1), a major target of SCRA. We measured CB1‐mediated activation of Gαs and Gαi/o proteins by SCRAs by examining stimulation (pertussis toxin, PTX treated) as well as inhibition (non‐PTX treated) of forskolin (FSK)‐induced cyclic adenosine monophosphate (cAMP) accumulation in human embryonic kidney (HEK) cells stably expressing CB1. Real‐time measurements of stimulation and inhibition of cAMP levels were made using a BRET biosensor. We found that the maximum concentration of SCRAs tested (10 µmol L −1 ), increased cAMP levels 12%‐45% above that produced by FSK alone, while the phytocannabinoid THC did not significantly alter cAMP levels in PTX‐treated HEK‐CB1 cells. All SCRAs had greater potency to inhibit FSK‐induced cAMP levels than to stimulate cAMP levels. The rank order of potencies for SCRA stimulation of cAMP (Gαs ) was PB‐22 > 5F‐MDMB‐PICA > JWH‐018 ≈ AB‐FUBINACA > XLR‐11. By contrast, the potency of SCRAs for inhibition of cAMP (Gαi/o ) was 5F‐MDMB‐PICA > AB‐FUBINACA > PB‐22 > JWH‐018 > XLR‐11. The different rank order of potency and EMax  of the SCRAs to stimulate Gαs ‐like signaling compared to Gαi/o signaling suggests differences in G protein preference between SCRAs. Understanding the apparent differences among these drugs may contribute to unravelling their complex effects in humans.